2020
DOI: 10.1038/s41598-020-61830-5
|View full text |Cite
|
Sign up to set email alerts
|

First trimester PAPP-A serum levels and long-term metabolic outcome of mothers and their offspring

Abstract: Low maternal serum levels of pregnancy associated plasma protein A (PAPP-A) are known to be associated with the development of pregnancy-related complications like small for gestational age infants, intrauterine fetal demise, gestational diabetes and preeclampsia. The study aims to find possible long-term correlations with the development of metabolic and cardiovascular complications in the mothers and their progeny in later life. This is a retrospective cohort study conducted on consecutive unselected women s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Altered serum levels of PAPP-A have been observed to be associated not only with FGR but also gestational diabetes and PE [222,223]. Long-term studies have found that this measurement is also associated with short stature in offspring and maternal diabetes mellitus in later life [224]. For this reason, this biomarker is key in the first trimester for a sooner prediction of placental health and prenatal outcomes to classify patients with increased risk of FGR [225].…”
Section: Screening Predictive and Diagnostic Biomarkersmentioning
confidence: 99%
“…Altered serum levels of PAPP-A have been observed to be associated not only with FGR but also gestational diabetes and PE [222,223]. Long-term studies have found that this measurement is also associated with short stature in offspring and maternal diabetes mellitus in later life [224]. For this reason, this biomarker is key in the first trimester for a sooner prediction of placental health and prenatal outcomes to classify patients with increased risk of FGR [225].…”
Section: Screening Predictive and Diagnostic Biomarkersmentioning
confidence: 99%
“…The incidence of chromosomal abnormalities, structural malformation and fetal loss will be significantly increased after the occurrence of horizontal abnormalities. [12][13] It was proposed in a study by Fruscalzo et al 14 that PAPP-A level changes may also occur in some pregnancy complications, such as placental abruption, spontaneous abortion, small-for-gestational age, premature rupture of membranes, stillbirth, preeclampsia, and fetal growth retardation suggesting that PAPP-A level changes have important scientific value in pregnation-related studies. 15 This study showed that the total incidence of preeclampsia and the incidence of early-onset preeclampsia, chromosome abnormality, fetal demise and smallfor-gestational age infants were significantly higher in the decreased PAPP-A group than in the normal PAPP-A group, and the incidence of chromosome abnormality and fetal demise was significantly higher in the increased PAPP-A group than in the normal control group, indicating that PAPP-A abnormality will increase the incidence of preeclampsia, chromosomal abnormalities, fetal demise, and small-for-gestational age infants.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal growth restriction, which complicates approximately 10% of all pregnancies, alongside preeclampsia, is a contributing factor to preterm deliveries [ 11 ]. Gestational diabetes mellitus and pregestational diabetes mellitus significantly impact pregnancy, maternal, and offspring outcomes (e.g., favoring pregnancy complications, abnormal fetal growth trajectories, or long-term sequels) [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%